INTEGRASI DZIKIR DAN FIKIR IMPLIKASINYA PADA PENDIDIKAN ISLAM - Miftahul Huda (Fakultas Agama Islam, Universitas Mathla'ul Anwar, 2023)
Islamic education is not oriented to the formation and development of aspects of human knowledge, but also the formation and development of spiritual aspects based on Islamic values ​​so that the process of Islamic education can give birth to humans who have noble character. For this reason, in the context of theology, there must be a balance between dhikr (spiritual) and fikr (intellectual) in the process of Islamic education. For this reason, this paper is intended to analyze the integration of dhikr and think about its implications for Islamic education. This study uses a qualitative research approach using library research techniques. The results of this study indicate that humans who are able to meditate and contemplate will reach a level that is able to understand and appreciate the wisdom behind phenomena in the universe is a form of God's power. In order for this goal to be achieved, the balance between dhikr and fikr must be maintained. In maintaining a balance between fikr and dhikr, the material in Islamic education must contain elements of mind education, physical education and heart education.